Aplicações de ressonância magnética nuclear (RMN) e quimiometria na determinação da autenticidade de uísques - Guimarães, Cainne Alves (2019)
More sophisticated products have been gaining the market with the increasing purchasing power of the population, and this consequently resulted in the triggering of sales and consumption of higher value-added beverages, among these, the whiskey showed greater increase in the national market, which gives it its high economic importance. In an attempt to compete and profit from the market, many gangs falsifying these products have been discovered by the Federal and Civil Police. However, several techniques have been applied in the investigation of fraud in beverages, but the pre-treatments of most of the samples are necessary for further analysis. In this context, NMR appears as a technique that can obtain information of a qualitative and quantitative nature simultaneously and for being a non-invasive method, not cause disturbance of balance and not be destructive, preserving the integrity of the sample. This work reports the application of NMR combined with chemometrics in the characterization and distinction of whiskey samples seized by the Federal Police of Brasilia and authentic commercial samples. Minority compounds observed in spectra performed with the suppression of water and ethanol allowed discrimination of the counterfeit samples. When performing an analysis of PCA and ERETIC2 per brand, it was possible to identify adulterated samples by dilution and those that were colored with caramel coloring. In conclusion NMR was useful in assessing the authenticity of whiskeys, in order to indicate changes in counterfeit beverage compositions.